2021
DOI: 10.1016/j.ribaf.2021.101486
|View full text |Cite
|
Sign up to set email alerts
|

Perceived vs actual financial crisis and bank credit standards: Is there any indication of self-fulfilling prophecy?

Abstract: We link senior banks loan officers' responses regarding their decisions for bank credit standards, from successive surveys from the European Bank Lending Survey to investigate two important issues. First, we examine the relationship between bank credit standards (CS) and perceived and actual financial crisis. Second, we investigate whether the notion of the self-fulfilling prophecy is applicable in the case of the 2008 global financial crisis. In particular, the second main research question that we try to ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The exploration of big data in general and social media analysis has been proven to be of great importance in analyzing the perception of both investors and bank customers (Illia, Colleoni, & Meggiorin, 2021). Specifically, academic and scientific investigations have focused on detecting attention and consumer attitudes using search volume generated by Google Trends (Anastasiou, Bragoudakis, & Giannoulakis, 2021). The amount of information that must deal with is quickly growing, primarily due to the development of the information sector, particularly the World Wide Web and mobile Internet.…”
Section: Introductionmentioning
confidence: 99%
“…The exploration of big data in general and social media analysis has been proven to be of great importance in analyzing the perception of both investors and bank customers (Illia, Colleoni, & Meggiorin, 2021). Specifically, academic and scientific investigations have focused on detecting attention and consumer attitudes using search volume generated by Google Trends (Anastasiou, Bragoudakis, & Giannoulakis, 2021). The amount of information that must deal with is quickly growing, primarily due to the development of the information sector, particularly the World Wide Web and mobile Internet.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Meierrieks (2014) reveals that financial development has a positive effect on innovation performance for 51 countries in the 1993-2008 period, and bank crises have no significant effect on innovation performance. Aristizabal-Ramirez et al (2017) examine the relationship between financial development and technological innovation at the firm level for 18 developing countries. Among the findings of the study, it is concluded that financial development has a negative effect on innovations for small firms.…”
Section: Introductionmentioning
confidence: 99%
“…However, a fast-growing literature has supported that private sector bank deposits are also affected by agents' economic sentiment, with some researchers support that sentiment exerts a higher impact on bank deposits than macro fundamentals. Our work is part of a growing strand of the literature that explores how the economic sentiment affects various facets of the economic activity (see among others, (Anastasiou, Ballis, & Drakos, 2021a, 2021cAnastasiou, Bragoudakis, & Giannoulakis, 2021b;Schumaker, Zhang, Huang, & Chen, 2012;Smales, 2014)) and especially to the literature investigating the impact of sentiment on bank deposits Anastasiou & Katsafados, 2020;Fecht, Thum, & Weber, 2019).…”
Section: Introductionmentioning
confidence: 99%